ANALYSIS OF THE IMPACT OF CIPALI TOLL ROAD ON ECONOMIC ACTIVITIES OF TRADE AND SERVICES IN THE PASSED AREA - Sya'bana, Isya'
The policy of accelerating infrastructure development is one of the general development policy directions in the RPJMN 2015-2019 and RPJMN 2020-2024 where one of the priority programs is toll road development with a target of 2,500 km of new toll roads built including the Trans Java toll road from Merak to Banyuwangi connected by 2024. The 116 km Cikampek-Palimanan (Cipali) toll road is part of the Trans Java toll road which has its own uniqueness, namely as the longest toll road in Java. In accordance with Government Regulation (PP) Number 39 of 2006 concerning Procedures for Control and Evaluation of the Implementation of Development Plans, the implementation of policies/programs/activities needs to be evaluated to assess its success where the success of public policy can be seen from the comparison between the results obtained with the objectives specified in the public policy, while according to PP Number 15 of 2005 concerning Toll Roads it is stated that the purpose of toll roads is to realize equitable development and increase efficiency in order to support increased economic growth, so it is very important to evaluate the impact of Cipali toll road development on the economy of the area through which it passes.